Quantitative Analysis of Total Phenolic Contents and Antioxidant Activity of Fresh Field Natural Rubber Latex. Issue 1 (25th August 2015) - Siriwong, Suwimon; Rungvichaniwat, Adisai; Klinpituksa, Pairote; Musa, Khalid Hamid; Abdullah, Aminah; Chirachanchai, Sawabu; Hoven, Voravee; Sojamsang, Warayuth
Summary Dried films of fresh field natural rubber latex from Pattani local rubber plantation, Thailand were prepared. The film (1g) was dissolved by various solvent (100ml) i.e. hexane, chloroform and mixtures of chloroform: methanol in the ratio of 1:1, 2:1 and 4:1. The solution was purified by separated the rubber out with methanol. The non‐rubber solution was then quantitative analyzed to verify total phenolic content (TPC), ferric reducing antioxidant power (FRAP) and DPPH radical scavenging activity using Oxicount Antioxidant kit test. It was found that only hexane, chloroform and mixture of chloroform: methanol of ratio 4:1 can dissolve rubber film completely. The non‐rubber content yields after evaporated solvent were 8.23 ± 0.05, 8.93 ± 0.81 and 11.56 ± 0.01%, TPCs were 226.18 ± 8.60, 230.91 ± 15.66 and 233.71 ± 12.44 milligrams of gallic acid equivalent (GAE) per 100 g of initial weight (IW) and FRAP were 153.04 ± 13.75, 178.43 ± 10.37 and 189.04 ± 1.34 milligrams of Trolox equivalents (TE) per 100 g of IW, the percentage of DPPH radical scavenging activity were 88.32 ± 0.99, 91.48 ± 0.86 and 92.42 ± 0.05%, respectively. This study found that TPC and antioxidant activity of rubber film clearly depend on the type of dissolved solvent. The highest antioxidant activity from this study was found by using the mixture of chloroform: methanol in the ratio of 4:1. Furthermore, the phenolic acid content of natural rubber were reported using HPLC, based on which more phenolic acids were presented in the sample extracted by chloroform:methanol mixture.